2019
DOI: 10.1002/cssc.201902279
|View full text |Cite
|
Sign up to set email alerts
|

Development of High‐Capacity and Water‐Lean CO2 Absorbents by a Concise Molecular Design Strategy through Viscosity Control

Abstract: The exponentially increasing viscosity of water‐lean CO2 absorbents during carbon capture processes is a critical problem for practical application, owing to its strong correlation with systems’ mass transfer properties, as well as convenience of transportation. In this work, a concise strategy based on structure–viscosity relationships is proposed and applied to construct a series of functionalized ethylenediamines as single‐component absorbents for post‐combustion CO2 capture. These nonaqueous absorbents hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 83 publications
0
9
0
Order By: Relevance
“…We have previously reported that tuning the speciation and hydrogen‐bond orientation can be used as critical molecular descriptor to decrease the viscosity of water‐lean solvents . Other groups have also derived new less viscous formulations based on these principles, showing that the viscosity of single‐component water‐lean solvents can be kept low by simple chemical modifications . The GAP‐1/TEG system differs from single‐component formulations in that it uses a cosolvent, although we hypothesize that the principles that govern viscosity are the same.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…We have previously reported that tuning the speciation and hydrogen‐bond orientation can be used as critical molecular descriptor to decrease the viscosity of water‐lean solvents . Other groups have also derived new less viscous formulations based on these principles, showing that the viscosity of single‐component water‐lean solvents can be kept low by simple chemical modifications . The GAP‐1/TEG system differs from single‐component formulations in that it uses a cosolvent, although we hypothesize that the principles that govern viscosity are the same.…”
Section: Introductionmentioning
confidence: 83%
“…[12] Other groups have also derived new less viscous formulations based on these principles, showing that the viscosity of single-component water-lean solvents can be kept low by simple chemical modifications. [13] The GAP-1/TEG system differs from single-component formulations in that it uses a co-solvent, though we hypothesized that the principles that govern viscosity are the same.…”
Section: Introductionmentioning
confidence: 99%
“…30 A viscosity of 124.0 mPa•S −1 was obtained for an N,N′-dimethyl-N-(2methoxyethyl) ethylenediamine (MeO-DMEDA)-based nonaqueous absorbent at its maximum CO 2 loading (0.7 mole CO 2 •mole amine −1 ). 31 While it is still high compared to that of aqueous MEA 32 (2.7 mPa•S −1 with 0.5 mole CO 2 •mole amine −1 at 40.0 °C), this is a substantial improvement for these water-lean absorbents and positions them for further investigations.…”
Section: Introductionmentioning
confidence: 92%
“…It is found that the viscosity of 1-alkyl-3-methylimidazolium tricyanomethanide ionic liquids ([C n mim]­[TCM], n = 2, 4, 6, 7, and 8) surprisingly decreased upon absorption of CO 2 , leading to an enhanced diffusion coefficient, which shows significant promise for utilization of this phenomena in industrial applications . A viscosity of 124.0 mPa·S –1 was obtained for an N , N′ -dimethyl- N -(2-methoxyethyl) ethylenediamine (MeO-DMEDA)-based non-aqueous absorbent at its maximum CO 2 loading (0.7 mole CO 2 ·mole amine –1 ) . While it is still high compared to that of aqueous MEA (2.7 mPa·S –1 with 0.5 mole CO 2 ·mole amine –1 at 40.0 °C), this is a substantial improvement for these water-lean absorbents and positions them for further investigations.…”
Section: Introductionmentioning
confidence: 99%
“…In our continuous efforts to develop new concepts as well as efficient strategies for CO 2 capture and further transformation, we envision that the viscosity of several traditional aliphatic amines at the CO 2 -saturated state could be significantly reduced though careful alkoxy functionalization. , The alkoxy arm embedded within the amine structure could create more free volume through its high conformational flexibility, thereby greatly enhance the flowability, and would ultimately intensify the interior mass transfer behavior to increase CO 2 capacity and thermoreversibility. , Ether-functionalized ionic liquids has also been separately studied for CO 2 /SO 2 capture through chemi- and/or physisorption. Meanwhile, carbamic acid is considered to be a feasible form of sequestrated CO 2 in the amine scrubbing process due to the full utilization of the nitrogen moiety (1:1 stoichiometry between CO 2 and nitrogen) and its relatively easy reversal compared with that of ammonium carbamate. ,, Furthermore, intramolecular hydrogen bonding is preferable if carbamic acid as an uncharged species dominates within the chemisorption system after CO 2 uptake, thus leading to lower operating viscosity than in the intermolecular hydrogen bonding scenarios . Notably, the alkoxy chain has been proved by recent reports to be a viable hydrogen bond acceptor that could bind the acidic proton to form multiple complexation. , We then propose a simple structural modification method for aliphatic primary amines that involves fixation of an appropriate alkoxy substituent to such a cheap and versatile industrial commodity, aiming to acquire reduced operating viscosity that enables smooth processing at the water-lean status under industrially relevant conditions and, in the meantime, increase capture capacity via stabilization of the in situ formed carbamic acid through intramolecular hydrogen bonding.…”
Section: Introductionmentioning
confidence: 99%